2016
DOI: 10.1038/srep31182
|View full text |Cite
|
Sign up to set email alerts
|

Beta rhythm modulation by speech sounds: somatotopic mapping in somatosensory cortex

Abstract: During speech listening motor regions are somatotopically activated, resembling the activity that subtends actual speech production, suggesting that motor commands can be retrieved from sensory inputs. Crucially, the efficient motor control of the articulators relies on the accurate anticipation of the somatosensory reafference. Nevertheless, evidence about somatosensory activities elicited by auditory speech processing is sparse. The present work looked for specific interactions between auditory speech presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…However, using electrocorticography (ECoG) it was shown that beta event-related desynchronization (ERD) is more focused and somatotopically specific than alpha ERD (Crone et al, 1998). More specifically and in line with our findings, somatotopic beta attenuation has also been shown for speech listening (Jenson et al, 2014;Bartoli et al, 2016). More specifically and in line with our findings, somatotopic beta attenuation has also been shown for speech listening (Jenson et al, 2014;Bartoli et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, using electrocorticography (ECoG) it was shown that beta event-related desynchronization (ERD) is more focused and somatotopically specific than alpha ERD (Crone et al, 1998). More specifically and in line with our findings, somatotopic beta attenuation has also been shown for speech listening (Jenson et al, 2014;Bartoli et al, 2016). More specifically and in line with our findings, somatotopic beta attenuation has also been shown for speech listening (Jenson et al, 2014;Bartoli et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The speaker role would elicit greater suppression in the alpha range, as often reported in behavioral synchronization tasks (Tognoli & Kelso, ). By contrast, the listener role would produce beta desynchronization, which has been associated to sensorimotor transformations during speech listening tasks (Bartoli, Maffongelli, Campus, & D'Ausilio, ) and top‐down predictive coding of upcoming sensory signals (Cope et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, oscillatory modulations in beta frequencies are supposed to reflect the close relationship between language comprehension and motor functions 36 . It has been shown that the beta rhythm modulation by speech sounds elicits a pattern in the somatosensory cortices of the listener that resembles the activity that subtends actual speech production in the speaker 37 . Furthermore, oscillations in the beta (and theta) band are instrumental in predicting the occurrence of auditory targets 38 .…”
Section: Discussionmentioning
confidence: 99%
“…As the motor and the somatosensory cortex have parallel somatotopies and with every articulator movement (performed under undeprived conditions) there is specific stimulation of the corresponding somatosensory cortex as well, this position predicts not only specific motor cortex activation in speech perception, but, in addition, somatosensory cortex activation. Indeed, there is evidence for a role of somatosensory systems both in speech production (Tremblay et al, 2003 ; Bouchard et al, 2013 ) and perception (Möttönen et al, 2005 ; Skipper et al, 2007 ; Ito et al, 2009 ; Nasir and Ostry, 2009 ; Correia et al, 2015 ; Bartoli et al, 2016 ). The motor and somatosensory system may already be important for speech perception early in life, since pacifiers blocking specific articulator movements were shown to affect the discrimination of speech sounds even in the first year (Yeung and Werker, 2013 ; for review see Guellaï et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%